Sign Language Learning Assessment Model Framework for Special Education Teacher - Syar Meeze Mohd Rashid; Noraidah Sahari @ Ashaari (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2018)
The purpose of this study is to obtain expert consensus and views on the elements of the sign language learning assessment model for special education teacher students. This study uses the Fuzzy Delphi method by using likert 5 scales to collect feedback from 30 experts in the field of pedagogical sign language in Malaysia. A total of 4 main elements of the questionnaire were given to the experts for evaluation. The Fuzzy Delphi method has been used to analyze the data. The data were analyzed using triangular fuzzy number and ranking with each model element determined by the “defuzzication” process. Analytical results of expert agreement and expert consensus have reached a very good consensus. The elements agreed upon by the experts on consensus are arranged in order of importance, expressive and receptive judgments, interaction assessments and written assessments.